Physical Property and Position Dependence of Low-field MR Imaging with Temporomandibular Joint Coil - Innami, Hisashi; Suzuki, Yu; Takahashi, Nobutoshi; Otaka, Yusei; Sezaki, Yusuke; Shinohara, Yuki; Okumura, Yasuhiro; Ozawa, Tomonori (Shika Hoshasen, 2012)
Objective: In this study we attempted to find the optimal settings for imaging the temporomandibular joint (TMJ) using open-type MRI with a TMJ coil. Methods: We took images using 0.2T open MRI and a TMJ coil with a phantom made of vegetable oil and distilled water. We took spin echo (SE) T1-weighted images (T1WI) at 400/17msec (TR/TE) T2WI 4000/150msec (TR/TE), with fields of view (FOV) of 240mm, 150mm, and 100mm, and number of signal averages (NSA) of 2, 4 and 6 for T1WI and 1, 2, 3, 4 and 5 for T2WI. We measured the signal-to-noise ratio (SNR) and modulation transfer function (MTF). Results: 1. The SNR increased in relation to the NSA, and decreased with increasing distance from the coil. 2. An expanded FOV resulted in an increased SNR. Comparison of the SNR in the slice closest to the coil (0 cm) and that farthest from the coil (5 cm) revealed striking differences in the width of increase and decrease. No marked differences were detected between T1-and T2-weighted images. 3. In images displaying large FOV, no meaningful differences were observed in the MTF curve based on the distance from the coil. The curve of images characterized by small FOV showed a distorted shape; thus, some variation based on the distance was evident. 4. The maximum spatial frequency declined in association with an increase in FOV (100mm: 1.2 cycles/mm, 150mm: 0.9 cycles/mm, 240mm: 0.5 cycles/mm). In addition, these results did not fluctuate greatly based on the distance from the coil. 5. Comparison of cases involving the placement of a temporomandibular coil on only one side with cases in which temporomandibular coils were positioned on both sides revealed smaller variations in the MTF curve of the latter. Conclusion: Acquisition of images ranging from those for screening the whole site to diagnosis of detailed parts by placement of coils in appropriate positions and alteration of the acquisition conditions in accordance with the objective was possible. The usefulness of this modality in the diagnosis of lesions directly underneath the body surface and in the temporomandibular region was well demonstrated.